The Role of Fnr Paralogs in Controlling Anaerobic Metabolism in the Diazotroph Paenibacillus polymyxa WLY78 - Shi, Haowen (Appl Environ Microbiol, 2020)
Fnr is a transcriptional regulator that controls the expression of a variety of genes in response to oxygen limitation in bacteria. Genome sequencing revealed four genes (fnr1, fnr3, fnr5, and fnr7) coding for Fnr proteins in Paenibacillus polymyxa WLY78. Fnr1 and Fnr3 showed more similarity to each other than to Fnr5 and Fnr7. Also, Fnr1 and Fnr3 exhibited high similarity with Bacillus cereus Fnr and Bacillus subtilis Fnr in sequence and structures. Both the aerobically purified His-tagged Fnr1 and His-tagged Fnr3 in Escherichia coli could bind to the specific DNA promoter. Deletion analysis showed that the four fnr genes, especially fnr1 and fnr3, have significant impacts on growth and nitrogenase activity. Single deletion of fnr1 or fnr3 led to a 50% reduction in nitrogenase activity, and double deletion of fnr1 and fnr3 resulted to a 90% reduction in activity. Genome-wide transcription analysis showed that Fnr1 and Fnr3 indirectly activated expression of nif (nitrogen fixation) genes and Fe transport genes under anaerobic conditions. Fnr1 and Fnr3 inhibited expression of the genes involved in the aerobic respiratory chain and activated expression of genes responsible for anaerobic electron acceptor genes. IMPORTANCE The members of the nitrogen-fixing Paenibacillus spp. have great potential to be used as a bacterial fertilizer in agriculture. However, the functions of the fnr gene(s) in nitrogen fixation and other metabolisms in Paenibacillus spp. are not known. Here, we found that in P. polymyxa WLY78, Fnr1 and Fnr3 were responsible for regulation of numerous genes in response to changes in oxygen levels, but Fnr5 and Fnr7 exhibited little effect. Fnr1 and Fnr3 indirectly or directly regulated many types of important metabolism, such as nitrogen fixation, Fe uptake, respiration, and electron transport. This study not only reveals the function of the fnr genes of P. polymyxa WLY78 in nitrogen fixation and other metabolisms but also will provide insight into the evolution and regulatory mechanisms of fnr in Paenibacillus.